AGASSIZ 1916 - Icelandic Association - North Dakota Agricultural College (Fargo, N.D.); Fargo (N.D.); (North Dakota State University Library, University Archives;, 1916)
1916 Agassiz 1916 Icelandic Association The Icelandic Association was organized in 1913, and since then has grown in strength and numbers. It holds enthusiastic meetings every Saturday in the basement of the library. They made their first public appearance in February, 1915, when they gave a tableau showing a typical home scene in Iceland thirty years ago; and thereby helped to entertain Mr. Percy McKeye, poet and dramatist, also Dr. Beede, the Indian missionary, at the first big banquet in the Little Country Theatre. The tableau was the first of a series of national programs that are intended to bring about a better understanding between the diverse foreign elements which form the population of our state.The Association also took a prominent part, representing Iceland, in the all-college colonial party given at the college armory, Feb. 20, 1915. These things are only a beginning. Bigger events are ahead. OFFICERS M. A. Thorfinnson, President B. F. Bjornson, Vice-President Anna Oddson, Secretary John Freeman, Treasurer MEMBERS Bjornson, B. K. Benson, Christian Benson, Margret Crookson, Victor Freeman, John Freeman, Wm. Freeman, Elizabeth Hjalmarson, H. H. Johnson, Anna Kristjanson, Gislina Kristjanson, Gudrun Magnuson, Augustine Magnuson, Hilda Myrdal, Einer Oddson, Anna Oddson, Lillie Reinholt, Emil Stefanson, Frida Thordarson, T. W. Thordarson, Gudrun Thordarson, Olivia Thordarson, Sigurdur Thorlakson, Gudrun Thorlakson, Thorum Thorfinnson, Theodore Thorfinnson, M. A. Viewbooks; 27 x 20 cm. Title taken from cover of book